CCNP Wireless (642-742 IUWVN) quick reference - Henry, Jerome (Cisco Press, 2012)
As a final exam preparation tool, the CCNP Wireless (642-742 IUWVN) Quick Reference provides a concise review of all objectives on the new exams. The short eBook provides readers with detailed, graphical-based information, highlighting only the key topics in cram-style format. With this document as your guide, you will review topics on concepts and commands that apply to this exam. This fact-filled Quick Reference allows you to get all-important information at a glance, helping you focus your study on areas of weakness and enhancing your memory retention of essential exam concepts. The IUWVN Implementing Cisco unified Wireless Voice Networks exam is an exam associated with the CCNP Wireless certification. CCNP Wireless certification addresses the need for designing, implementing, and operating Cisco Wireless networks and mobility infrastructures. CCNP Wireless certification emphasizes wireless networking principles and theory. It also recognizes the expertise and technical acumen of wireless professionals who can assess and translate network business requirements into technical specifications that in turn, are incorporated into successful installations.